OP37 Is the withdrawal of anti-tumour necrosis factor in inflammatory bowel disease patients in remission feasible without increasing the risk of relapse? Results from the randomised clinical trial of GETECCU (EXIT). (30th January 2023) - Chaparro, M; García Donday, M; Riestra, S; Lucendo, A J; Benítez, J M; Navarro-Llavat, M; Barrio, J; Morales-Alvarado, V J; Rivero, M; Busquets, D; Leo Carnerero, E; Merino Ochoa, O; et al.
Abstract: Background: Background: The feasibility of anti-TNF discontinuation in inflammatory bowel disease (IBD) must be proven in clinical trials including patients in clinical, endoscopic, and radiologic remission at the time of anti-TNF withdrawal to make recommendations for clinical practice. Aims: Primary: to compare the rates of clinical remission at 1 year in patients who discontinue anti-TNF treatment vs. those who continue treatment. Secondary objectives: to know the effect of anti-TNF withdrawal on relapse-free time, mucosal healing and safety; and to identify predictive factors for relapse. Methods: Prospective, quadruple-blind, multicentre, randomised, controlled trial. Patients with ulcerative colitis (UC) or Crohn's disease (CD) in clinical remission for > 6 months were randomised to maintain anti-TNF treatment [maintenance arm (MA)] or to withdraw it [withdrawal arm (WA)]. Patients who were on infliximab (IFX) received IFX 5 mg/kg or an intravenous placebo every 8 weeks, while patients on adalimumab (ADA) received subcutaneous ADA 40 mg or placebo every other week. Patients were followed-up until month 12 or up to the time of clinical relapse, whichever came first. Inclusion and exclusion criteria, trial scheme and definitions are summarized in figures 1a, 1b and 1c. Results were analysed by intention-to-treat (ITT) and by per-protocol (PP). Local investigators were blinded to faecal calprotectin (FC) and IFX and ADA trough levels. On-site monitoring was performed to assess data quality. Results: 159 patients were screened, from whom 140 were randomised and comprised the ITT cohort: 70 allocated to the MA and 70 to the WA. Fifteen patients dropped out before the end of follow-up (12 months or relapse), leaving 63 patients in the MA and 62 patients in the WA for the PP analysis. The characteristics of patients in the MA and WA were similar (figure 2). The proportions of patients who maintained clinical remission -59/70 (84%), 95% confidence interval (CI)=74-92% in the MA vs. 53/70 (76%), 95%CI=64-85% in the WA- and who remained without significant endoscopic lesions at the end of follow-up were similar between groups (figures 3a, 3b, 3c). Only the proportion of patients with FC >250 mg/g was higher in the WA at the end of follow-up (figure 3d). Maintenance of clinical remission was no different between groups (figure 4). The same percentage of patients in both groups had at least one adverse event (69%). The proportion of patients with serious adverse events was also similar between groups (4% in MA vs. 7% in WA). Conclusion: Anti-TNF withdrawal in selected IBD patients in clinical, endoscopic, and radiologic remission could be feasible without an increase in the risk of clinical relapse. Long-term follow-up of these patients is warranted.